Development of a mussel-inspired conductive graphene coated cotton yarn for wearable sensors - Guanliang He; Chuang Zhu; Yuze Shi; Yingjia Yu; Yi Wu; Constantinos Soutis; Le Cao; Xuqing Liu (iScience)
Summary: Graphene-based flexible yarn sensors are promising due to their exceptional conductivity and user-friendly properties, but ensuring stable graphene adsorption on fibers for long-term durability remains challenging. Herein, we produce a flexible polydopamine (PDA)-modified cotton yarn via a simple dip-coating process using a self-made sodium deoxycholate (SDC)-modified graphene dispersion, avoiding non-biodegradable, corrosion-prone metallic coatings. The resulting sensor exhibits low electrical resistance (as low as 21.1Ω ± 0.2/cm), high bending sensitivity (resistance change rate of 3.557 ± 0.002 for bending ranges from 40% to 100%), and outstanding durability over 2,000 flexural bending cycles. It can monitor various human body movements and physiological states and be integrated into wearable electronic textiles (e-textiles) for applications like monitoring knee movements, recognizing hand gestures, and detecting thoracic respiratory status. This work highlights the sensor’s potential in personal and public healthcare applications.